2013
DOI: 10.3390/ijms140918959
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying Activity and Stability of a Non-Toxic Bioemulsifier Synthesized by Microbacterium sp. MC3B-10

Abstract: A previously reported bacterial bioemulsifier, here termed microbactan, was further analyzed to characterize its lipid component, molecular weight, ionic character and toxicity, along with its bioemulsifying potential for hydrophobic substrates at a range of temperatures, salinities and pH values. Analyses showed that microbactan is a high molecular weight (700 kDa), non-ionic molecule. Gas chromatography of the lipid fraction revealed the presence of palmitic, stearic, and oleic acids; thus microbactan may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Camacho-Chab et al (2013) studying the genus Microbacterium isolated from marine environment reported the production of glycoproteins able to emulsify aromatic hydrocarbons and oils. The emulsifier isolated from the marine environment differs from the biosurfactant isolated in this work as showed by the absorption bands obtained by FTIR, probably due to the environment differences.…”
Section: Bacterial Strain Investigated For the Production Of Biosurfamentioning
confidence: 99%
See 1 more Smart Citation
“…Camacho-Chab et al (2013) studying the genus Microbacterium isolated from marine environment reported the production of glycoproteins able to emulsify aromatic hydrocarbons and oils. The emulsifier isolated from the marine environment differs from the biosurfactant isolated in this work as showed by the absorption bands obtained by FTIR, probably due to the environment differences.…”
Section: Bacterial Strain Investigated For the Production Of Biosurfamentioning
confidence: 99%
“…Hassanshahian, Giti, and Simone (2011), Kumar, Mamidyala, Sujitha, Muluka, and Akkenapally (2012) and Wongwongsee, Chareanpat, and Pinyakong (2013) reported the formation of emulsifiers for this genus, though they did not appraise the quantity or the type produced. Also Camacho-Chab et al (2013) have isolated bacteria of the genus Microbacterium from marine environments and identified a compound classified as microbatan. However, there are no reports on biosurfactant production by bacteria of this gender in Amazonian freshwater environment, which are contaminated by hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…MC3B-10 was characterized previously to have surfactant activity against aliphatic hydrocarbons and hinted at a potential metal-binding activity [154]. This EPS was termed microbactan and was extensively characterized [155]. Bioassay-based toxicity testing showed that microbactan is not toxic.…”
Section: Eps-based Products For Aquaculture Applicationsmentioning
confidence: 99%
“…Although extensive researches have been conducted on variety of aspects of different bioemulsifiers including production, emulsification activity and cell surface hydrophobic activities, however, few analysis of the field application of bioemulsifiers based on the emulsification activity and production were carried out further. The most likely application of bioemulsifier was in MEOR [2,3], which of low requirements toward the emulsifier concentration and purity. Bioemulsifiers played a significant role in extracting the remaining oil from oil reservoirs, which was cost-effective, environmental-friendly, and efficient particularly in the exploitation of oil remained trapped in capillary pores of the formation rock or in areas not swept by the classical or modernenhanced oil recovery (EOR) methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to form stabilized o/w or w/o emulsion and keep the condition was the typical feature of these substances, which ensured its potential application in microbial-enhanced oil recovery (MEOR) [2,3]. Plentiful studies about bioemulsifiers nowadays were done which mainly focused on isolation, screening of active strains, and the characteristics of their products [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%